Incidence of Microemboli and Correlation with Platelet Inhibition in Aneurysmal Flow Diversion - Levitt, M.R.; Ghodke, B.V.; Hallam, D.K.; Sekhar, L.N.; Kim, L.J. (American Journal of Neuroradiology, 2013)
SUMMARY: Flow-diverting stents have been associated with embolic and hemorrhagic complications, but the rate of procedure-related microemboli is unknown. Using transcranial Doppler sonography, we measured the rate of microemboli in 23 patients treated with flow-diverting stents. Patients received preprocedural dual antiplatelet medications and intraprocedural heparinization. Point-of-care platelet reactivity testing was performed before the procedure, and nonresponders (>213 P2Y12/ADP receptor reactivity units) received additional thienopyridine. Transcranial Doppler sonography was performed within 12–24 hours. Microemboli were detected in 3 patients (13%), 2 of whom were initially nonresponders. There was no association between the presence of microemboli and procedural or neurologic complications, aneurysm size, number of stents, or procedure time. Eight procedures (34.8%) required additional thienopyridine for inadequate platelet inhibition, and 3 required further treatment for persistent nonresponse to point-of-care platelet reactivity testing. There were 6 technical and 2 postoperative complications; none were associated with inadequate platelet inhibition or microemboli. The combination of routine point-of-care platelet reactivity testing and postprocedural microembolic monitoring may help identify patients at risk for thromboembolic complications after flow-diverting stents. FDSflow-diverting stentPRTpoint-of-care platelet reactivity testingPRUP2Y12/adenosine diphosphate receptor reactivity unitsTCDtranscranial Doppler sonography